2011
DOI: 10.1139/x11-103
|View full text |Cite
|
Sign up to set email alerts
|

The effects of methyl bromide alternatives on soil and seedling pathogen populations, weeds, and seedling morphology in Oregon and Washington forest nurseries

Abstract: Five fumigation treatments (a conventional methyl bromide -chloropicrin application and four reduced-rate alternative fumigant treatments) and a nonfumigated treatment were evaluated at two forest nurseries in Oregon and one forest nursery in Washington for their effects on soil pathogen populations, weeds, and seedling morphology during a 2-year study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…In that study, 100 isolates were originally selected at random from each of the three nurseries (nursery A in southwestern Washington and nurseries B and C in northwestern Oregon) and from each of three isolation methods used at each nursery (dilution plating and baiting with rhododendron leaf disks or Douglas-fir needle segments) to yield 900 total isolates (300 isolates from each nursery). These three species were also chosen based on their association with damping-off disease of conifers in previous studies (20,41,44,45), and their presence in comparatively large numbers at more than one nursery during the 2008 survey (43). Isolates were subsequently selected for this study as representatives of 16 of the 19 species found at the three nurseries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, 100 isolates were originally selected at random from each of the three nurseries (nursery A in southwestern Washington and nurseries B and C in northwestern Oregon) and from each of three isolation methods used at each nursery (dilution plating and baiting with rhododendron leaf disks or Douglas-fir needle segments) to yield 900 total isolates (300 isolates from each nursery). These three species were also chosen based on their association with damping-off disease of conifers in previous studies (20,41,44,45), and their presence in comparatively large numbers at more than one nursery during the 2008 survey (43). Isolates were subsequently selected for this study as representatives of 16 of the 19 species found at the three nurseries.…”
Section: Methodsmentioning
confidence: 99%
“…cause damping-off and root rot in forest seedling nurseries worldwide and are considered one of the most important soilborne pathogens affecting tree seedling production (41,(44)(45)(46). cause damping-off and root rot in forest seedling nurseries worldwide and are considered one of the most important soilborne pathogens affecting tree seedling production (41,(44)(45)(46).…”
mentioning
confidence: 99%
“…Iodomethane with chloropicrin has been successful in soil disease and weed control, in both spring (80:20 at 275 pounds per acre) and fall applications (50:50 at 175 to 350 pounds per acre) (unpublished industry data and Weiland et al 2011).…”
Section: 3-dichloropropene (13-d)mentioning
confidence: 99%
“…Much of the groundwork was accomplished by R. L. James and colleagues, who identified pathogenic species of Fusarium and Pythium (e.g., James 2002). More recently, a number of new Fusarium and Pythium species have been described from forest nursery soils (Weiland 2011;Weiland et al 2011), and research has identified eight Pythium species that are virulent pathogens of Douglas-fir seedlings (Weiland et al 2013).…”
Section: Research Needsmentioning
confidence: 99%
See 1 more Smart Citation